(untitled) (Academia Journal of Medicine, 2026)
Background: Denture base resins play a critical role in the longevity and clinical success of removable prostheses. Conventional heat-cured polymethyl methacrylate (PMMA) has long been the material of choice; however, the advent of 3D printing technology has introduced alternative materials with potential advantages in fabrication efficiency and customization. Despite these benefits, concerns remain regarding their mechanical properties. Aim: To compare the mechanical strength of 3D-printed denture base resins with conventional heat-cured denture base resins. Materials and Methods: This in vitro study was conducted using standardized rectangular specimens fabricated from two groups: Group I – heat-cured PMMA denture base resin and Group II – 3D-printed denture base resin. Each group consisted of equal numbers of samples prepared according to manufacturer specifications. Mechanical strength was evaluated using a three-point bending test on a universal testing machine to determine flexural strength. The obtained data were statistically analyzed using an independent t-test, with the level of significance set at p < 0.05. Results: The heat-cured PMMA group demonstrated higher mean flexural strength compared to the 3D-printed resin group. The difference between the groups was found to be statistically significant (p < 0.05), indicating superior mechanical performance of conventional denture base material under the tested conditions. Conclusion: Within the limitations of this study, heat-cured denture base resins exhibited greater mechanical strength than 3D-printed resins. However, 3D-printed materials offer advantages in terms of fabrication and digital workflow, suggesting the need for further advancements to enhance their mechanical properties for long-term clinical application.